Sources and requirements of professional competencies for information specialists in the library sector: an analytical study - khoudour, samir; .bensebti, abdelmalek. (Journal of Social Sciences and Humanities, 2023)
This study aims to determine the skills necessary for an information specialist, whether he occupies the position of first level attaché in university libraries or archivist librarian in public libraries, according to three fundamental sources: the Configuration Offers of national harmonization and its output of skills, as well as various legislation related to the profession of Librarians in the sectors of culture and higher education, in addition to this, the repositories to the professions which are among the important management tools in the workplace that determine the people who must be present in an establishment with their tasks and the skills that must be provided there